Keefektifan Model Think Pair Share Berbantu Media Gaser Terhadap Keterampilan Menulis Siswa - Rizqi Uswatun Khasanah; Sutrisno Sutrisno; Mudzanatun Mudzanatun (Universitas Ngudi Waluyo, 2018)
Abstract: The purpose of this research is to know the effectiveness of think pair share model assisted media gaser to writing skill of class V student of SD Negeri 06 Randudongkal Pemalang. This research is a quantitative research using One Group Pretest Posttest Design research design using one class as research subject. he results of this study were obtained by performing initial data analysis, normality test with lilliefors test, and final data analysis with T test. Based on the analysis of final data that has been done calculation T test obtained t count> ttable is 13,16> 1,687, hence hypothesis can be accepted, thereby can be concluded that study with model Think Pair Share assist Gaser media effective to writing skill class V SD Negeri Randudongkal Pemalang.Keywords: Think Pair Share models, glowing images, writing skills